Photic zone changes in the north-west Pacific Ocean from MIS 4–5e - Swann, G.E.A.; Snelling, Andrea M. (European Geosciences Union, 2015)
In comparison to other sectors of the marine system, the palaeoceanography of the subarctic North Pacific Ocean is poorly constrained. New diatom isotope records of δ13C, δ18O δ30Si (δ13Cdiatom, δ18Odiatom and δ30Sidiatom) are presented alongside existing geochemical and isotope records to document changes in photic zone conditions, including nutrient supply and the efficiency of the soft-tissue biological pump, between Marine Isotope Stage (MIS) 4 and MIS 5e. Peaks in opal productivity in MIS 5b/c and MIS 5e are both associated with the breakdown of the regional halocline stratification and increased nutrient supply to the photic zone. Whereas the MIS 5e peak is associated with low rates of nutrient utilisation, the MIS 5b/c peak is associated with significantly higher rates of nutrient utilisation. Both peaks, together with other smaller increases in productivity in MIS 4 and 5a, culminate with a significant increase in freshwater input which strengthens/re-establishes the halocline and limits further upwelling of sub-surface waters to the photic zone. Whilst δ30Sidiatom and previously published records of diatom δ15N (δ15Ndiatom) (Brunelle et al., 2007, 2010) show similar trends until the latter half of MIS 5a, the records become anti-correlated after this juncture and into MIS 4, suggesting a possible change in photic zone state such as may occur with a shift to iron or silicon limitation.